2020
DOI: 10.1038/s41419-019-2219-4
|View full text |Cite
|
Sign up to set email alerts
|

UCP2-induced hypoxia promotes lipid accumulation and tubulointerstitial fibrosis during ischemic kidney injury

Abstract: Mitochondrial dysfunction leads to loss of renal function and structure; however, the precise mechanisms by which mitochondrial function can regulate renal fibrosis remain unclear. Proximal tubular cells (PTCs) prefer fatty acid oxidation as their energy source and dysregulation of lipid metabolism has been linked to tubulointerstitial fibrosis (TIF). Here, we demonstrated that mitochondrial uncoupling protein 2 (UCP2) regulates TIF through the stimulation of lipid deposition and extracellular matrix (ECM) acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…Ucp1 is highly abundant in brown and beige adipocytes in vivo, while Ucp2 is ubiquitously expressed across various tissues and cell types 27 , 28 . Gene targeting and RNA interference approaches have indicated that UCP2 has a weak uncoupling activity, but UCP2 is physiologically required for different functions such as regulation of mitochondrial oxidative stress and energy metabolism 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Ucp1 is highly abundant in brown and beige adipocytes in vivo, while Ucp2 is ubiquitously expressed across various tissues and cell types 27 , 28 . Gene targeting and RNA interference approaches have indicated that UCP2 has a weak uncoupling activity, but UCP2 is physiologically required for different functions such as regulation of mitochondrial oxidative stress and energy metabolism 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Ke et al reported that UCP2 expression is increased in human biopsy samples and mice kidney tissues with tubulointerstitial fibrosis but UCP2 deficient mice display reduced lipid accumulation and attenuated hypoxia in kidney tissue. Compared with wildtype mice, the expression of PPARα and CPT1α, which are the major regulators of lipid metabolism, is restored in UCP2 deficient mice (Ke et al, 2020). Both CPT1 and ACO2 are the rate-limiting enzymes of FA β-oxidation.…”
Section: Dysregulated Mitochondrial Lipid Utilization In Kidney Diseasesmentioning
confidence: 94%
“…Primary PTECs were cultured from collagenase-digested cortical fragments of mice (about 21 days) kidneys according to a modified method previously described [ 20 , 21 ]. In brief, after been dissected and collagenase digested, two nylon sieves with the pore sizes of 250 and 80 μm were used to yield proximal tubule fragments, which were then washed, resuspended, and seeded onto collagen-coated permeable PTFE-filter supports and cultured for 48 h in a standard humidified incubator with the medium replaced every 2 days till the organization of a confluent monolayer of cells.…”
Section: Methodsmentioning
confidence: 99%
“…OCT-embedded kidney tissues were sectioned at 12 μm for oil red O (Sigma-Aldrich, US) and 3 μm for bodipy (D3922, Thermo Fisher, US) staining as previously described [ 6 , 21 , 25 ]. Nuclei were viewed by alum haematoxylin staining.…”
Section: Methodsmentioning
confidence: 99%